THE MEDIATING EFFECT OF PLACE ATTACHMENT ON THE RELATIONSHIP BETWEEN SENIOR CITIZEN ACTIVITY INVOLVEMENT AND ACTIVITY SATISFACTION - A CASE FROM THE PERSPECTIVE OF LEISURE MANAGEMENT - Chen, Yi-Chen; Chiang, Ching-Wen (International Journal of Application on Economics and Business, 2023)
At present, most countries in the world regard aging in place as the main goal of the elderly society. Meanwhile, senior citizens are encouraged to participate in community activities, and long-term care (LTC) resources are provided in the community. Previous studies have also mentioned that activity involvement and place attachment are more likely to affect activity satisfaction Therefore, the purpose of this study is to use place attachment as the mediating variable to explore the influence of the relationship between activity involvement and activity satisfaction. By the survey method, a total of 400 questionnaires were sent out, and 387 valid questionnaires were recovered. The analysis results revealed that activity involvement and place attachment has a significant positive influence with activity satisfaction respectively. Place attachment only has a mediating effect on the relationship between the self-expression (dimension of activity involvement) and the psychological satisfaction (dimension of activity satisfaction). Relevant management suggestions are also put forward.